Communist political propaganda and use of United States mails. Hearing before the Subcommittee to Investigate the Administration of the Internal Security Act and Other Internal Security Laws, of the Committee on the Judiciary, United States Senate. Eighty-sixth congress, first session. and use of United States Mails. [Testimony of Irving Fishman], March 26, 1959 (United States Government Printing Office, 1959)
With index and tabs.